Social Financial Grant and Poverty Alleviation in South Africa: Array - Ngwakwe, Collins; IQBAL, BADAR, A (Acta Universitatis Danubius. Œconomica, 2021)
financial grant is seen as an avenue to reduce poverty, inequality and to improve equitable economic development. Objective. The objective of this paper is to examine the effect of social financial grant increases on poverty alleviation in South Africa. Prior work. The paper inclines on the poverty theories of economic growth, which highlights the use of social financial grants to achieve poverty reduction and equitable economic growth. Approach. The paper applies a quantitative approach; data on social grants were collected from the publications of the South African department of statistics and the South African social security agency. The ensuing cross-sectional data were analysed using the structural equation modelling approach. Findings: the findings indicate that, amongst the seven types, only three namely, the grants for old age, grants for disability and grants for supporting a child enhances reduction in inequality. On the contrary, four of the seven social grant types enhances reduction in poverty level; these are the grants for war veterans, aid grants, grants for dependency and grants for fostering a child. Implications. The paper highlights policy implications of the findings, which includes inter alia, that policy makers may target poverty reduction or inequality reduction using specific social grant types. Findings from this paper provide an avenue for further research to assess poverty and inequality reduction through these social grant types in other developing economies. Such research should check if this current research result, which is based on South African data is replicable using social grant data from other developing countries. Value. This paper uniquely applies the SEM model to evaluate poverty and inequality implication of social grants in South Africa.